Peran Media Pembelajaran dan Permainan dalam Meningkatkan Motivasi Belajar Siswa - Sultonurohmah, Nina (BASICA, 2023)
A media is an intermediary or anything that is used for a process of transmitting messages or information that can stimulate students' thoughts, feelings and will so that it can encourage teaching and learning. Apart from learning media, games that are connected to learning material are also very helpful in creating interesting and enjoyable learning. Such games that involve students are: exploratory play, dynamic play (energetic play), skillful play, social play, imaginative play, and puzzle games. -it-out play). Through games, students' thinking and socializing abilities can be improved. Motivation in the learning process is also very necessary to make learning enjoyable. Teachers can provide motivation in the classroom in the form of: giving points, praise, prizes, group work, competition, goals and level of aspiration, sarcasm, assessments, field trips and excursions, educational films and learning via radio. The role of learning media and games in increasing student motivation in class is very necessary to eliminate feelings of boredom and saturation in learning. With media, games and motivation provided by the teacher, learning will be interactive, meaningful and fun and students will easily accept the teacher's explanations, the teacher will also be helped in explaining the material.